A atuação dos profissionais de relações públicas da Secom na comunicação do governo do estado do Rio Grande do Sul - (:unkn) unknown (Universidade Federal do Pampa, 2014)
This study presents a case study that aims to understand the dynamics of working of SECOM and also make a investigation regarding the activities that perform the Public Relations. In this sense, we chose to perform in-depth interviews with these professionalsmethod that identified serious flaws in the professional practice like the fact that these servers were displaced persons to other functions and fail to make the activities who seek the relationship between organizations and their publics. After a brief institutional analysis of the Secretariat the Communications of the Government the State of the Rio Grande do Sul (SECOM) it was observed that this organ does not have in its institutional activities the professionals Public Relations (PR) as participants of the practices that theoretically they would be of the area . Thereafter began a search theories job for deepening on the issue of Governmental Communication and Public Relations, it was possible to to have them based for this diagnosis.
Keywords: Relações Públicas; Trabalho qualificado; Prática profissional; Rio Grande do Sul. Secretaria de Comunicação e Inclusao Digital; Marketing de relacionamento; Comunicação na administração pública; Public relations; Skilled work; CNPQ::CIENCIAS SOCIAIS APLICADAS